Polyester Sulphonic Acid Interstitial Nanocomposite Platform for Peroxide Biosensor - Emmanuel I. Iwuoha; Priscilla G. L. Baker; Nazeem Jahed; Amir Al-Ahmed; Peter M. Ndangili (Sensors, 2009)
A novel enzyme immobilization platform was prepared on a platinum disk working electrode by polymerizing aniline inside the interstitial pores of polyester sulphonic acid sodium salt (PESA). Scanning electron microscopy study showed the formation of homogeneous sulphonated polyaniline (PANI) nanotubes (~90 nm) and thermogravimetric analysis (TGA) confirmed that the nanotubes were stable up to 230 °C. The PANI:PESA nanocomposite showed a quasi-reversible redox behaviour in phosphate buffer saline. Horseradish peroxidase (HRP) was immobilized on to this modified electrode for hydrogen peroxide detection. The biosensor gave a sensitivity of 1.33 μA (μM)-1 and a detection limit of 0.185 μM for H2O2. Stability experiments showed that the biosensor retained more than 64% of its initial sensitivity over four days of storage at 4 °C.